DITIS: A Distributed Tiered Storage Simulator - Lucas Filho, Edson Ramiro; Odysseos, Lambros; Lun, Yang; Kebo, Fu; Herodotou, Herodotos (My University, 2022)
This paper presents DITIS, a simulator for distributed and tiered file-based storage systems. In particular, DITIS can model a distributed storage system with up to three levels of storage tiers and up to three additional levels of caches. Each tier and cache can be configured with different number and type of storage media devices (e.g., HDD, SSD, NVRAM, DRAM), each with their own performance characteristics. The simulator utilizes the provided characteristics in fine-grained performance cost models (which are distinct for each device type) in order to compute the duration time of each I/O request processed on each tier. At the same time, DITIS simulates the overall flow of requests through the different layers and storage nodes of the system using numerous pluggable policies that control every aspect of execution, ranging from request routing and data redundancy to cache and tiering strategies. For performing the simulation, DITIS adapts an extended version of the Actor Model, during which key components of the system exchange asynchronous messages with each other, much like a real distributed multi-threaded system. The ability to simulate the execution of a workload in such an accurate and realistic way brings multiple benefits for its users, since DITIS can be used to better understand the behavior of the underlying file system as well as evaluate different storage setups and policies.
Keywords: Distributed Data Storage; Performance Cost Models; Storage Simulator; Tiered Storage